Design for manufacture and assembly - Koeisch, James R.; Dewhurst, Nicholas (Manufacturing insights)
Design for manufacture and assembly (DFMA) is a proven design methodology used to optimize part costs and quality, while reducing time-to-market development. This program features an interview with Nicholas Dewhurst of Boothroyd Dewhurst and explains the concepts and use of DFMA in product analysis to understand the drivers of cost, and the interaction of the individual pieces within the product to optimize design, manufacturability, and assembly.